Towards an ultra lightweight block ciphers for Internet of Things. (September 2021) - Sliman, Layth; Omrani, Tasnime; Tari, Zahir; Samhat, Abed Ellatif; Rhouma, Rhouma
Abstract: Conventional cryptographic methods are not appropriate for IoT environments due to the specific IoT devices constraints, such as memory usage, time and computational costs. This leads to the emergence of the lightweight cryptography field. This paper investigates the different lightweight cryptographic design methods and proposes an IoT-based cryptographic method, called Ultra-Lightweight method (ULM), to enhance the performance, memory usage and security of IoT devises. The proposed method is based on three methods (i.e, bitslice, WTS and involutive), and thus accumulating their various advantages such as, memory use, efficiency and security. To validate our proposal, a cryptosystem is designed using ULM method. The designed cryptosystem is benchmarked based on the following metrics: performance (by measuring its execution time and the number of clock cycles needed to run it), the quantity of used memory (by measuring ROM and RAM consumption), and security level (by measuring its diffusion and confusion levels along with its resistance to linear and differential attacks). The results show that the cryptosystem designed using the proposed method outperforms existing methods in terms of memory use, security and performance.